Evaluating Healthcare Safety Under Article 462 of Law 17 of 2023 in the Digital Health Transformation Era - Striratna Candra Wilasita; Happy Yulia Anggraeni (Research Horizon, 2026)
Law Number 17 of 2023 concerning Health marks a massive transformation in Indonesian health law by consolidating a previously fragmented legal system into a single omnibus scheme. This study aims to comprehensively analyze these regulatory modifications, identify new legal strengths, and evaluate structural flaws within medical professional protection. Utilizing a normative-doctrinal legal research method with a qualitative-descriptive approach, this study examines the vertical and horizontal synchronization of legal materials governing healthcare occupational safety. The findings demonstrate that although the new statute expands normative rights and prioritizes restorative justice alongside upstream professional disciplinary screening, this integration is severely flawed by critical ambiguities in Article 462 Paragraph (1). The failure to define operational boundaries for medical negligence (culpa levis and culpa lata), combined with loose frameworks for cross-border data transfers and organ transplantation, undermines the principle of legal certainty. In conclusion, this legal ambiguity fosters anxiety over premature criminalization and drives inefficient defensive medicine practices, making the meticulous drafting of derivative regulations that safeguard clinical autonomy imperative.